Properties, techniques, and applications of polyaniline (PANI) thin films emerging research and opportunities - Chander, Subhash; Jangid, Nirmala Kumari (IGI Global, 2020)
"This book examines high-throughput synthesis of PANI thin films and their characterization techniques. It also explores applications of PANI thin films and applications including solar cells"--